Field evaluation of rice lines derived from Suakoko 8 X Bao Thai for iron tolerance in the South Saharan African farming system - Sikirou, M.; Shittu, A.; Moukoumbi, Y.D.; Arouna, A.H.; Zokpon, C.; Bocco, R.; Najimu, A.; Ramaiah, V. (MDPI, 2024)
Rice is a major grain crop in numerous countries. In lowland areas, high iron levels in the soil severely hinder its cultivation. The current study explored high-yielding and Fe-toxicity-tolerant irrigated lowland rice (340 lines) among a population derived from a cross between Suakoko 8 and Bao Thai in Edozighi and Ibadan, Nigeria. In contrast to Ibadan, the soils in Edozighi contain a significant amount of iron. For the stated purpose, we carried out a two-year experiment using an alpha lattice design. The data showed significant differences between genotypes for the days to heading, plant height, number of tillers per plant, number of panicles per plant, panicle length, and grain yield. The results revealed that multiple characteristics had both direct and indirect effects on cultivated rice yields. There was a direct and positive influence on the number of days in the 50% heading period (0.31), a direct and negative effect on plant height (−0.94), a direct and positive effect on tiller and panicle numbers, and a direct but negative effect on panicle length (−0.56). The leaf bronzing score was adversely correlated with yield, panicle length, and plant height, while it was positively correlated with the number of panicles, tillers, and days to heading. The findings showed significant changes in yield and yield characteristics between genotypes. Grain yields ranged from 283 to 11,700 kg/ha in the absence of iron in the soil, contrary to 0 to 8230 kg/ha in soil with iron toxicity, with losses estimated between 6 and 94%, demonstrating the resulting disaster. In contrast to the elite parents and varieties used in this study, the ten top genotypes exhibited smaller losses in yield. The authors strongly recommend using these lines for further studies as donors or releasing them in farmer fields in Africa.